LIQUID CONSUMPTION IN THE PLATFORM ECONOMY: A COMPARATIVE CASE STUDY OF THREE PLATFORMS AND SIX USER GROUPS - Lutz, Christoph; Stocker, Volker (AoIR Selected Papers of Internet Research, 2023)
The notion of “liquid consumption” draws on Bauman’s theory of liquid modernity to describe shifts in consumer behavior in recent years. Liquid consumption is contrasted to more traditional “solid” consumption and is characterized by ephemerality (rather than endurance), access (rather than ownership), and dematerialization (rather than material possessions). Despite the popularity of liquid consumption theory and the prominent role of digital platforms in shaping liquid consumption, a thorough analysis how digital platforms enable or constrain liquid consumption is missing. In our research, we address this gap and study the role of liquidity on three key digital platforms in the platform economy: Airbnb, Uber, and Fiverr. The research relies on a comparative case study method and is informed by the walkthrough approach, answering three distinct research questions: 1. How inherent is liquidity in a certain product/service category in the first place (pre-platform)? 2. Where do different platforms fall on the dimensions of the liquid-solid consumption spectrum? 3. How does the solidity/liquidity of the consumption/use/experience differ between providers and consumers?